2017
DOI: 10.1080/02646838.2017.1383977
|View full text |Cite
|
Sign up to set email alerts
|

Premature birth: complexities and difficulties in building the mother–child relationship

Abstract: Our results underline that preterm birth could be a risk factor for the co-construction of interactive exchanges between mother and premature baby. This study could help practitioners to better consider parental roles and to carry out specific supportive interventions for both parents and children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 44 publications
4
43
0
6
Order By: Relevance
“…After birth, the mother normally initiates specific behaviours towards her newborn, aimed at supporting the neonate who experiences high levels of stress during hospitalisation in the NICU,39 and at fostering the infant’s socioemotional development 40 41. However, mothers of preterm infants may present difficulties in developing these protective behaviours 42. Thus, parental stress may interfere with the infant’s socioemotional and cognitive development, and is associated with more difficulties in building positive parent–infant relationships due to disrupted interactions 40 43 44.…”
Section: Developmental Carementioning
confidence: 99%
“…After birth, the mother normally initiates specific behaviours towards her newborn, aimed at supporting the neonate who experiences high levels of stress during hospitalisation in the NICU,39 and at fostering the infant’s socioemotional development 40 41. However, mothers of preterm infants may present difficulties in developing these protective behaviours 42. Thus, parental stress may interfere with the infant’s socioemotional and cognitive development, and is associated with more difficulties in building positive parent–infant relationships due to disrupted interactions 40 43 44.…”
Section: Developmental Carementioning
confidence: 99%
“…In accordance with the results of this study, mothers of preterm infants showed a higher level of obsession (M preterm birth = 4.07 ± 0.74, M full-term birth = 4.39 ± 0.51, t = 2.22, p = 0.029) and remoteness (M premature babies = 4.45 ± 0.83, M full-term babies ) = 4.79 ± 0.34, t = 2.51, p = 0.015) than mothers of full-term children. From the data obtained, the researchers conclude that preterm delivery can be a risk factor for the interactive relationship between a mother and a premature baby [2].…”
Section: Introductionmentioning
confidence: 98%
“…As a result, their parents suffer from emotional distress, depression, and anxiety at higher rates than parents of healthy infants and can develop altered parenting patterns on discharge home [4][5][6][7][8] . These negative outcomes particularly affect the mothers who are more likely to be the primary caretaker [9][10][11] . These infants also face higher risk of hospital readmission and death during the first year after birth 12,13 .…”
Section: Introductionmentioning
confidence: 99%